Assessment of Brachial Plexus Dose and Associated Toxicity in Nasopharyngeal Carcinoma Radiotherapy - Besbes, Marwa; Mousli, Alia; Abidi, Fathia; Asma, Zidi; Ben zid, Khedija; Ghorbel, Asma; Soussi, Mohamed; Saidi, Sarra; MOKRANI, Cyrine; ATTIA, Najla; Abidi, Rim; Nasr, Chiraz (F1000 research, 2025)
Introduction Radiation plexopathy is known to depend on various parameters, and is rarely reported in head&neck cancers. While literature suggests dose constraints of 60-66 Gy, our study aimed to evaluate late brachial plexopathy after primary chemoradiotherapy for locally advanced nasopharyngeal carcinoma with IMRT, and determine the maximum tolerated dose. Methods Between May 2015 and March 2020, a retrospective cohort of 50 patients with a history of previously irradiated nasopharyngeal cancer was identified. All patients underwent definitive treatment using IMRT at recommended curative doses. Clinical and treatment-related characteristics were collected, and all cases were reviewed for symptoms of radiation-induced brachial plexopathy. Verbal informed consent was obtained from all patients prior to their inclusion in the study. Results Of the 50 patients, 98% received concurrent chemoradiotherapy. The mean age at treatment was 44 years. All patients received a maximum dose of ≥ 60 Gy. The maximum dose to the BP (BPmax) was 82.64 Gy (mean: 72.8 Gy). The mean dose received by 0.03 cm 3 of the BP was 71.74 Gy. Among patients with nodal involvement, 86% received a maximum dose of ≥ 66 Gy. A correlation study with N-category showed a significant increase in BPmax dose with increasing nodal stage. The mean BPmax for patients with level III/IV lymph nodes (75.19 Gy) was higher than for those with level I/II involvement (69.19 Gy) (P = 0.0001). All patients had a minimum follow-up of two years, with a mean follow-up duration of 37.5 months. Five patients reported clinical symptoms of acute or late brachial plexopathy, but none had confirmation via MRI or electromyography. Conclusion In our study using IMRT for nasopharyngeal cancer patients and with a minimum follow-up of two years, it appears safe to deliver > 66 Gy to the brachial plexus. However, longer follow-up is required.